1977
DOI: 10.1111/j.1600-0528.1977.tb01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and gingival health in Danish dental students and faculty

Abstract: This survey attempted to determine the status of oral cleanliness and gingival health in 150 dental students and 101 faculty members in a dental school. Without advance notice, plaque deposits were scored, using the Plaque Index System, and gingival health was determined using the criteria of the Gingival Index System. The 1st-year students had the poorest hygiene and gingival health. An improvement (P less than 0.01) was noted in the 2nd-year students who were still not in clinical training but had completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
2
22
1
Order By: Relevance
“…It has been shown that plaque removal is least effective on the approximal and lingual surfaces after manual toothbrushing (Cumming & Loe 1973, Lang et al 1977, Rugg‐Gunn et al 1979). This was confirmed in the present study, with the highest mean percentage plaque removal achieved at the mid‐facial sites and the lowest from the approximal lingual/palatal sites regardless of whether a new or a 3‐month‐old brush head was used.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that plaque removal is least effective on the approximal and lingual surfaces after manual toothbrushing (Cumming & Loe 1973, Lang et al 1977, Rugg‐Gunn et al 1979). This was confirmed in the present study, with the highest mean percentage plaque removal achieved at the mid‐facial sites and the lowest from the approximal lingual/palatal sites regardless of whether a new or a 3‐month‐old brush head was used.…”
Section: Discussionmentioning
confidence: 99%
“…Though dental students are constantly educated on preventive dentistry, results indicate that students' oral health improves only after entering clinical training and might deteriorate until graduation. 6 It was shown that an average senior student's oral health was fairly good; however, a number of students with very poor oral hygiene were recorded as well. 6 In an attempt to explain this phenomenon, it is important to consider the fact that the dental study program is one of the most intense study programs requiring an ability to memorize a lot of information as well as the ability to handle emotional stress related to clinical experience.…”
mentioning
confidence: 99%
“…6 It was shown that an average senior student's oral health was fairly good; however, a number of students with very poor oral hygiene were recorded as well. 6 In an attempt to explain this phenomenon, it is important to consider the fact that the dental study program is one of the most intense study programs requiring an ability to memorize a lot of information as well as the ability to handle emotional stress related to clinical experience. Individual capability to handle these environmental challenges results in different levels of perceived stress, fatigue or sleep disorders and is likely to influence oral health-related behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, dental students, in general, incline to have better oral hygiene and are supposedly better motivated than the general population, and consequently any changes in gingival bleeding and plaque inhibition before and after therapy may be assumed to have been slight and hence could have influenced the results. In order to minimize this limitation, the sample was randomly drawn from 1st and 2nd year students who tend to have a poorer oral hygiene than their senior counterparts [19]. …”
Section: Discussionmentioning
confidence: 99%